PEDAGOGICAL CONTENT OF PREPARING PRIMARY CLASS STUDENTS FOR CREATIVE ACTIVITY (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
In this article, the ways of forming the creative activity of primary school students, the preparation of students of junior school age for the process of creative activity, its pedagogical importance, the methodology of developing creativity in students, and how to make children of the present age creative Brief measures aimed at increasing speech to thinking are given